Zakat Fundraising Strategy: Opportunities and Challenges in Digital Era - Mohammad Soleh (Journal of Nahdlatul Ulama Studies, 2020)
This research aimed at providing a new perspective on the fundraising strategy of zakat through its opportunity and challenge approach in the digital era, by analyzing and identifying existing problems in the previous zakat fundraising strategy, as an effort to reduce the gap between the potential and realization of zakat fundraising in Indonesia. This was a literary study by using a qualitative descriptive analysis method based on library research. This research succeeded in finding and identifying the problem of zakat fundraising strategies in zakat institutions, namely; 1) the need to improve organizational governance; 2) institutional strengthening; and 3) seizing opportunities and challenges in the digital era by transforming digital fundraising technology. The findings of this study can be a recommendation in perfecting zakat fundraising strategies to be applied to zakat institutions. This paper also recommends the perpetrators of Islamic philanthropy to work together with the government in formulating various efforts to optimize the fundraising of zakat and its distribution on target.